Strategies associated with improved healthiness of consumer purchasing in supermarket interventions: a systematic overview of reviews and evaluation of primary articles - Brooker, Paige G.; Howlett, Caitlin A.; Brindal, Emily; Hendrie, Gilly A. (Frontiers in Public Health, 2024)
Background Growing evidence suggests that it is possible to change the retail food environment to enable healthier choices via in-store interventions. The aim of this study was to (1) summarise current high-quality systematic, scoping, and/or narrative reviews (Part I: overview of reviews); and (2) synthesise high-quality original research, to understand the range, types and effectiveness of strategies implemented in food retail settings (Part II: evaluation of primary studies). Methods To identify reviews describing the effects of intervention strategies aiming to improve the healthiness of consumer purchasing in supermarkets, a systematic search across seven electronic databases was completed in April 2023. The methodological quality of reviews was assessed using the Risk of Bias In Systematic Reviews for systematic and scoping reviews, and the Scale for the Assessment of Narrative Review Articles for narrative reviews. High-quality reviews were further inspected and synthesised narratively (Part I). Next, to understand strategies associated with improved healthiness of consumer purchasing high-quality, primary articles from high-quality reviews identified in Part I were retrieved, and the strategies implemented within these interventions were summarised (Part II).Results Thirty-eight reviews met the inclusion criteria for Part I; two-thirds (n=25, 66%) were rated as high-quality (66%). These reviews indicated that pricing strategies had the greatest proportion of reported positive or promising effects on outcomes (n=8 of 11 reviews, 73%). Twenty reviews met the inclusion criteria for Part II and the 771 primary articles from these reviews were screened with 23 high-quality primary articles included in analysis. Findings indicated that promotional strategies in combination with another strategy appeared to be most successful among regular shoppers (the general population), whereas pricing was most successful in low socio-economic status and rural sub-groups.Conclusions Promotion, pricing and prompting were the most commonly tested strategies across the overview of reviews and review of primary articles. Promotion, in combination with other strategies, and pricing appear to be most promising, but the effectiveness of pricing strategies may vary by sub-groups of the population. How pricing and promotion in combination with other strategies can be implemented responsibly and sustainably to change purchase habits toward healthier items should be explored further.